Congenital intestinal pseudo-obstruction associated with a giant platelet disorder. Issue 7 (July 1991) - Pollock, I; Holmes, S J K; Patton, M A; Hamilton, P A; Stacey, T E
Abstract : In this report we present a patient with the unique combination of chronic intestinal pseudo-obstruction and congenital thrombocytopenia with a non-specific type of giant platelet disorder.